Annemarie Johansen’s Stages of Growing up: Lois Lowry’s Number the Stars as a Bildungsroman - Dinar Tri Nugraheni; Bernadus Hidayat (Lexicon, 2018)
This research examines Lois Lowry’s Number the stars, focusing on the development of Annemarie Johansen’s self-awareness and personality trait from the stage of immaturity into maturity. In line with the topic of research, the formalist approach was used as the main theoretical approach. The library research was used in collecting the data. To point out every crucial stage of Annemarie Johansen’s growing up process, the definition of Bildungsroman proposed by Dilthey (1985) was applied. The results reveal that Annemarie Johansen goes through stages of growing up processes from her immaturity into maturity throughout violent and dangerous times. The results also show that during her self-growth, Annemarie Johansen gradually develops her self-awareness and personal trait of being a courageous girl in order to survive in the harsh reality and she manages to save her good friend, Ellen, from the plan of Nazi persecution of Jews during the German occupation. Finally, she transforms herself from an innocent and frightened girl into a brave girl in a brief period.